Role of TLR2 and TLR4 in Human Neutrophil Functions Against Paracoccidioides brasiliensis - Acorci-Valerio, M. J. [UNESP]; Bordon-Graciani, A. P. [UNESP]; Dias-Melicio, L. A. [UNESP]; Golim, M. de Assis [UNESP]; Nakaira-Takahagi, E. [UNESP]; de Campos Soares, A. M. V. [UNESP] (Wiley-Blackwell Publishing, Inc, 2010)
In paracoccidioidomycosis, a systemic mycosis caused by the fungus Paracoccidioides brasiliensis (Pb), studies have focused on the role of neutrophils that are involved in primary response to the fungus. Neutrophil functions are regulated by pro- and anti-inflammatory cytokines. The molecular mechanisms involved in this process are not fully understood, but there are strong evidences about the involvement of toll-like receptors (TLR). We aimed at evaluating TLR2 and TLR4 expression on human neutrophils activated with GM-CSF, IL-15, TNF-alpha or IFN-gamma and challenged with a virulent strain of P. brasiliensis (Pb18). Moreover, we asked if these receptors have a role on fungicidal activity, H(2)O(2) and IL-6, IL-8, TNF-alpha and IL-10 production by activated and challenged cells. All cytokines increased TLR2 and TLR4 expression. Pb18 also increased TLR2 expression inducing an additional effect to that of cytokines. on the contrary, it inhibited TLR4 expression. All cytokines increased neutrophil fungicidal activity and H(2)O(2) production, but this process was not associated with TLR2 or TLR4. Neutrophils activation with GM-CSF and TNF-alpha resulted in a significative increase in IL-8 production, while IL-15 and IFN-gamma have no effect. Pb18 alone also increased IL-8 production. None of the cytokines activated neutrophils for IL-10 release. This cytokine was only detected after Pb18 challenge. Interestingly, IL-8 and IL-10 production involved TLR2 and mainly TLR4 modulation. Our data suggest that Pb18 uses TLR4 to gain access to human neutrophils. This interaction results in IL-8 and IL-10 production that may be considered as a pathogenic mechanism in paracoccidioidomycosis.